PENGARUH GAYA KEPEMIMPINAN TRANSAKSIONAL DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT.ESTA DANA VENTURA AREA SERANG - Indah Diana; Suflani Suflani; Hadi Kurniawanto (LP2M Universitas Bina Bangsa, 2023)
Human Resources (HR) is the main center in carrying out a job in a company or organization.PT. Esta Dana Ventura is a center and training center, which is engaged in non-bank financial institutions, with a venture capital model / microfinance institute. PT. Esta Dana Ventura was established on February 9, 2015, EDV's first office is located at the BSD Junction shophouse Blok A No/11 Serpong Tangerang. In this study, the authors took samples using a saturated sampling technique. Another term for saturated sample is census, where all members of the population are sampled, which is 42 people. This type of research is field research with quantitative descriptive methods, namely research that is intended to describe (describe) a problem. Based on the results of the research above, the results of the partial test (t test) have a tcount of 1.836 and a t-table of 2,02269 (tcount > ttable) with a significance value of 0.001 (sig. < 0.05), and the value of the partial test results (t-test) the value of tcount is 2,677 and ttable is 2,02269 (tcount > ttable) with a significance value of 0.001 (sig. <0.05). So it can be concluded that Ho is rejected and Ha is accepted. And the value of the simultaneous test results (F test) the Fcount value is 5.670 and Ftable is 3.24 (Fcount > Ftable) and with a significance value of 0.000 (sig. <0.05). So it can be concluded that Ho is rejected and Ha is accepted. The results of this study can be concluded that the Transactional Leadership Style (X1) and Work Discipline (X2) have an effect on Employee Performance (Y), either partially or simultaneously at PT. Esta Venture Fund